Proton therapy achieves high-dose tumor control with organ preservation in complex metastatic adenoid cystic carcinoma: a case report of a refractory patient with 16 pulmonary metastases - Lu, Zejun; Zhang, Xuanrong; Jiang, Zhiqiang; Chu, Haiqiang; Li, Lei; Wang, Zishen; Xie, Yingrong; Ren, Bin; Kang, Jingbo (Frontiers in Oncology, 2025)
Adenoid Cystic Carcinoma (ACC) is characterized by its aggressive nature, high propensity for perineural invasion, and significant risk of distant metastasis, particularly to the lungs. Therapeutic options for locally advanced or metastatic ACC are limited, and conventional radiotherapy is often constrained by dose limitations for multifocal disease, leading to inadequate treatment. A 54-year-old male ACC patient, who had recurred after three prior surgeries, presented with PET/CT-confirmed bilateral cervical lymph node and multiple bilateral pulmonary metastases. Given the multifocal metastases and the critical need for sparing organs at risk (lungs, heart, esophagus), which rendered photon radiotherapy unable to meet the required dose constraints, proton therapy was employed with the following dose prescriptions: for pulmonary metastases: CTV 50 Gy(RBE) in 15 fractions, GTV 60 Gy(RBE) in 15 fractions; for the cervical lesion: GTVnd 70 Gy(RBE) in 28 fractions, CTVnd 66 Gy(RBE) in 28 fractions, CTV 50.4 Gy(RBE) in 28 fractions. Follow-up PET/CT post-treatment demonstrated complete resolution of some bilateral pulmonary metastases, with marked reduction in size and decreased metabolism in the remaining nodules. The metastatic cervical lymph nodes also showed reduced volume and metabolic activity. No adverse events exceeding Grade 2 occurred during the treatment course. This case demonstrates that proton therapy is highly suitable for multifocal ACC metastases, especially multiple small pulmonary nodules. Through its precise dose delivery, it enables high-dose irradiation (GTV 60–70 Gy(RBE)) to targets while significantly sparing normal organs. This approach represents a viable strategy for complex cases where conventional radiotherapy is contraindicated. It aims to delay disease progression and achieve organ preservation in refractory ACC.